Effect of African swine fever on genetic diversity in Black Slavonian pig - Škorput, Dubravko; Stupnišek, Ivan; Špehar, Marija; Karolyi, Danijel; Kaić, Ana; Luković, Zoran (Frontiers in Animal Science, 2025)
African swine fever (ASF) is a highly contagious viral disease affecting domestic and wild pigs, leading to high mortality rates and significant economic losses. Local pig breeds, such as the Black Slavonian pig, are particularly vulnerable due to increased contact with wild boar. This study aimed to assess the genetic diversity parameters of Black Slavonian pigs in Eastern Croatia following a recent ASF outbreak using pedigree-based analyses. Pedigree data comprising 13,306 animals were analyzed, with a reference population of 1,658 individuals from 2018 onward. Genetic diversity parameters, including the average inbreeding coefficient, average relatedness, and effective population size, were estimated under two scenarios: one assuming no ASF-related culling and another excluding animals culled due to ASF. An optimal contribution selection procedure was applied to minimize relatedness within the population, and mating plans were developed for both scenarios to estimate future inbreeding and relatedness. The average inbreeding coefficient was 5.21% in the scenario without ASF-related culling and 4.27% in the scenario with ASF-related culling. Effective population size was 47.10 in the first scenario and 42.94 in the second, indicating a reduction in genetic diversity. Despite the slightly improved genetic diversity parameters in the ASF scenario, the reduced number of mating candidates increased the risk of inbreeding due to a higher likelihood of pairing related individuals. While genetic diversity remained relatively stable, the results suggest that ASF-related culling influenced population structure by removing highly related animals. However, the long-term impact on genetic variability requires further investigation. Future studies incorporating molecular genetic data would enhance the accuracy of relatedness estimation, as pedigree-based analyses may over- or underestimate genetic diversity due to shallow ancestry records.